2017
DOI: 10.1074/jbc.m117.784470
|View full text |Cite
|
Sign up to set email alerts
|

The R753Q polymorphism in Toll-like receptor 2 (TLR2) attenuates innate immune responses to mycobacteria and impairs MyD88 adapter recruitment to TLR2

Abstract: Toll-like receptor 2 (TLR2) plays a critical role in host defenses against mycobacterial infections. The R753Q TLR2 polymorphism has been associated with increased incidence of tuberculosis and infections with non-tuberculous mycobacteria in human populations, but the mechanisms by which this polymorphism affects TLR2 signaling are unclear. In this study, we determined the impact of the R753Q TLR2 polymorphism on macrophage sensing of Upon infection with, macrophages from knock-in mice harboring R753Q TLR2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 61 publications
0
15
1
Order By: Relevance
“…Furthermore, the TLR2 polymorphism R753Q is associated with a severe phenotype and higher levels of IgE in AD patients . Others showed an altered function of MyD88 signaling in mice macrophages bearing the TLR2 polymorphism R753Q . It has been reported that the frequency of R753Q is higher in AD children, while others showed a similar distribution in healthy children and concluded that the association between AD and R753Q is lacking .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the TLR2 polymorphism R753Q is associated with a severe phenotype and higher levels of IgE in AD patients . Others showed an altered function of MyD88 signaling in mice macrophages bearing the TLR2 polymorphism R753Q . It has been reported that the frequency of R753Q is higher in AD children, while others showed a similar distribution in healthy children and concluded that the association between AD and R753Q is lacking .…”
Section: Discussionmentioning
confidence: 99%
“…For infections, wild‐type (WT) or IRAK4 KI mice were i.p. administered M. smegmatis (5 × 10 6 CFUs) or L. monocytogenes (2 × 10 4 CFU), similar to doses used in previous reports . Six hours post infection (hpi), blood samples were obtained by retroorbital punctures and serum was prepared to analyze cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…Six hours post infection (hpi), blood samples were obtained by retroorbital punctures and serum was prepared to analyze cytokines. At 48 hpi, spleens and livers were homogenized in PBS containing protease and phosphatase inhibitors (ThermoFisher Scientific, Waltham, MA) and bacterial CFUs were enumerated by plating organ homogenates on the respective agars . To generate bone marrow‐derived macrophages (BMDMs), bone marrow cells from femurs and tibias were differentiated for 7 days in DMEM (Mediatech, Herndon, VA), supplemented with 10% FBS (Atlanta Biologicals, Flowery Branch, GA), 2 mM l ‐glutamine, 100 U/ml penicillin, 100 μg/ml streptomycin (complete RPMI) and 15% L929 cell‐conditioned, macrophage‐colony‐stimulating factor‐containing supernatant …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR 2 is taken part in immunity against infection of MTB. The capability of toll like receptor 2 to contribute in the white blood cells triggering by MTB and different responses mediation activated by these cells propose that protein of TLR may work discrete functions in the mycobacteria immune responses [10]. A study showed that TLR 2 existence is unessential for increasing sufficient inherited resistance to aerobic infection with M. tuberculosis [11].…”
Section: Introductionmentioning
confidence: 99%